2021
DOI: 10.5937/ekonomika2101027g
|View full text |Cite
|
Sign up to set email alerts
|

The Internet promotion of Moravica administrative district as a tourism destination

Abstract: Tourism destinations tend to create and represent the integrated product of tourism appropriately. The target market can often be outside the national borders. In such circumstances, modern promotion in tourism requires flexibility, as well as the creation of optimum communication strategy. Such strategies include the combination of the Internet and the traditional forms of promotinal activities. It is necessary to highlight websites and social networks as the basic, often the most important elements of the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The results showed that PME elements significantly contributed to increasing DA on IVHD. Effective advertising and well-targeted sales promotions can increase tourists' knowledge and awareness about Halal destinations, creating greater interest in visiting them (Garabinović and Milićević, 2021).…”
Section: Promotion-mix Elements (Pme) Destination Awareness (Da) and ...mentioning
confidence: 99%
“…The results showed that PME elements significantly contributed to increasing DA on IVHD. Effective advertising and well-targeted sales promotions can increase tourists' knowledge and awareness about Halal destinations, creating greater interest in visiting them (Garabinović and Milićević, 2021).…”
Section: Promotion-mix Elements (Pme) Destination Awareness (Da) and ...mentioning
confidence: 99%